2016
DOI: 10.1098/rsta.2015.0428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rock mineralogy and pore structure on stress-dependent permeability of shale samples

Abstract: We conducted pulse-decay permeability experiments on Utica and Permian shale samples to investigate the effect of rock mineralogy and pore structure on the transport mechanisms using a non-adsorbing gas (argon). The mineralogy of the shale samples varied from clay rich to calcite rich (i.e. clay poor). Our permeability measurements and scanning electron microscopy images revealed that the permeability of the shale samples whose pores resided in the kerogen positively correlated with organic content. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…However, current simulation practices extract only < 25% of gas and < 10% of the oil estimated in the formation (Kuuskraa et al 2013), and it is hypothesized that low matrix diffusivity might contribute to the low overall recovery efficiency (Karra et al 2015). Geophysical studies have demonstrated that hydrocarbon flow through shale matrices is affected by different rock compositions and pore structures, and involves complex transport mechanisms such as Knudsen diffusion, slip flow, and gas adsorption/desorption (Fathi et al 2009, Villazon et al 2011, Swami et al 2012, Heller et al 2014, Guo et al 2015, Zhang et al 2015, Al Ismail et al 2016, Huang et al 2016, Wu et al 2017. From the perspective of geochemistry, both mineralogical composition and pore structure of shale matrices can be altered by chemical reactions, affecting hydrocarbon flow in shale matrices.…”
Section: Introductionmentioning
confidence: 99%
“…However, current simulation practices extract only < 25% of gas and < 10% of the oil estimated in the formation (Kuuskraa et al 2013), and it is hypothesized that low matrix diffusivity might contribute to the low overall recovery efficiency (Karra et al 2015). Geophysical studies have demonstrated that hydrocarbon flow through shale matrices is affected by different rock compositions and pore structures, and involves complex transport mechanisms such as Knudsen diffusion, slip flow, and gas adsorption/desorption (Fathi et al 2009, Villazon et al 2011, Swami et al 2012, Heller et al 2014, Guo et al 2015, Zhang et al 2015, Al Ismail et al 2016, Huang et al 2016, Wu et al 2017. From the perspective of geochemistry, both mineralogical composition and pore structure of shale matrices can be altered by chemical reactions, affecting hydrocarbon flow in shale matrices.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this progression, unconventional shale reservoir production remains highly inefficient, with industry reported recovery factors of around 25% for gas (Rassenfoss, 2018) and rapid rate declines a few years after initial production (Valko and Lee, 2010), suggesting that a large portion of the resource is still left trapped, as adsorbed gas, inside the nanopores of the shale matrix (Ambrose et al, 2010). Although shale mineral composition is considered to be a main factor controlling shale permeability (Ismail and Zoback, 2016;Chalmers et al, 2012), there is a shortage of experimental work looking at fracture fluid chemical reactions on shale matrix permeability of intact cores with varying mineral composition. In this study, our goal is to understand how fracture fluid affects the permeability of the shale matrix from either porosity enhancement or mineral precipitation due to the shale's mineral composition.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental setup set inside temperature control box for hydrostatic permeability measurements (left) (Image from: AlIsmail and Zoback, 2016). Sample microcore epoxied onto PTFE annulus adapter to fit into core holder and batch reactor (right).…”
mentioning
confidence: 99%
“…Without losing of generality, we selected c m = 0.08 MPa −1 in this case. The measured pore size ranges from about 20 nm to 200 nm according to several experiments [13,22]. Therefore, the value of 60 nm is used as the pore radius in this case.…”
Section: The Coupled Effect Of Poro-elastic Compaction and Slip Flowmentioning
confidence: 99%